2001
DOI: 10.1046/j.0269-283x.2001.00319.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of the buffalo fly Haematobia irritans exigua in India, using the pyrethroids deltamethrin and fenvalerate

Abstract: The effectiveness of two pyrethroids, fenvalerate and deltamethrin, against the fly Haematobia irritans exigua de Meijere (Diptera: Muscidae) on buffalo was considered in a field trial. Fenvalerate provided 100% control for 1, 2 and 4 weeks at concentrations of 0.03, 0.04 and 0.05%, respectively. Concentrations of 0.01 and 0.02% were less effective. One hundred percent control of this fly was obtained with deltamethrin for 2, 3 and 6 weeks at concentrations of 0.003, 0.004 and 0.005%, respectively. Deltamethri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Kano et al (1972) reported that the presence of long hairs on the second segment of the hind tarsi of male is a differentiating character between H. exigua and H. irritans. Parashar et al (2001) and Low et al (2017) have also reported that H. exigua is prevalent in India and Southeast Asia. Out of 239 ies examined, 101 and 138 ies were male and female respectively.…”
Section: Resultsmentioning
confidence: 93%
“…Kano et al (1972) reported that the presence of long hairs on the second segment of the hind tarsi of male is a differentiating character between H. exigua and H. irritans. Parashar et al (2001) and Low et al (2017) have also reported that H. exigua is prevalent in India and Southeast Asia. Out of 239 ies examined, 101 and 138 ies were male and female respectively.…”
Section: Resultsmentioning
confidence: 93%